PERLINDUNGAN HUKUM BAGI PRODUSER FONOGRAM AQUARIUS: STUDI PUTUSAN MAHKAMAH KONSTITUSI NOMOR 84/PUU-XXI/2023: Legal Protection for Aquarius Phonogram Producers: A Study of Constitutional Court Decision No. 84/PUU-XXI/2023 - Gunawan, Cheryl Natasya; Bustami, Simona (AMICUS CURIAE, 2025)
Legal protection for phonogram producers is crucial due to their significant role in the music industry, Legal protection for phonogram producers is crucial because they play a significant role in the music industry, responsible for financing, producing, and publishing sound recordings (phonograms). Phonogram producers hold the related rights to the recorded songs and/or music they produce, which necessitates legal protection. Copyright and related rights violations in Indonesia can be exemplified by the case between PT Aquarius Musikindo and Bigo Technology Pte. Ltd. The aim of this research is to illustrate the legal protection for Aquarius' phonogram producers over their recorded works, based on Law No. 28 of 2014 concerning Copyright (2014 Copyright Law) and the Constitution Law No. 28 of 2014 concerning Copyright (2014 Copyright Law) and the Constitutional Court Decision No. 84/PUU-XXI/2023 (MK Decision). The research methodology is normative legal research with a descriptive nature. The primary data in this study are secondary data, supported by primary data, analyzed qualitatively, and conclusions are drawn deductively. In the effort to protect phonogram producers, the MK Decision states that Article 10 of the 2014 Copyright Law is conditionally contradictory to Article 28D paragraph (1) of the 1945 Constitution. This research shows that the Constitutional Court has expanded the interpretation of marketplace, where digital platforms based on user-generated content (UGC) are now equated with traditional marketplace operators. These operators are not permitted to sell, display, and/or duplicate goods that infringe copyrights and/or neighboring rights without authorization.